A STUDY ON RELATIONSHIP BETWEEN SELF-ESTEEM AND SOCIAL CONNECTEDNESS AMONG POSTGRADUATES (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
The study examines that an Individual with low self-esteem may have less opportunity for interactions which lead to anxiety and depression therefore, developing social connections considered an important part for an individual’s better level of self-esteem. Realizing the role of social connection on self-esteem, a multidisciplinary approach is required to initiate appropriate interventions in building self-esteem. Method of analysis includes the Descriptive Statistic’s such as correlation, chi-square test. Measurement and calculations can be found in the appendix. The research draws attention to that Self-Esteem and social connectedness is associated and dependent with each other; the correlation also reveals that as one variable goes up other will come down and as one variable goes down other will go up, so there is an inverse relationship between both the variables; Also, on the basis of study as compare to female, male have High self-esteem with a better social connectedness therefore gender is dependent on Self-Esteem as well as Social connectedness. The study found that there is a relationship between self-esteem and Social connectedness. Students who have high Self-esteem are tends to be socially connected, find it desirable to surround themselves with others, also investigated the fact that the analysis conducted has limitations, also the study constitutes to students, in a college which may lead to insufficient availability of primary data since limited to the respondents and study will focus on social connections from the individual’s perspective to enhance the self-esteem.